(untitled) (Annals of Bangladesh Agriculture, 2025)
The study investigated the effect of temperature, time, and pH to find an optimum condition for pectin extraction from Colombo lemon peel. The extracted pectin was also analyzed for their physicochemical characteristics. The functional groups of the pectin were located using FTIR spectroscopy. Pectin was extracted from the dried peel powder using 95% ethanol at different combinations of time (20 mins, 40 mins and 60 mins), temperature (60°C, 80°C and 100°C), and pH (2, 2.5 and 3.0). Optimal conditions for pectin extraction were determined to be 80°C, 60 mins, and pH 2 for Colombo lemon peel yielding up to 15.2% pectin. The moisture content, ash content, equivalent weight, methoxyl content, anhydrouronic acid content, degree of esterification, acetyl value and water activity of the Colombo lemon peel pectin were 13.30%, 2.45%, 819.67 mg/mol, 7.25%, 62.66%, 65.60%, 0.45%, 0.46% respectively. The findings of this study suggest the suitability of extracted pectin from Colombo lemon peel to be used in food preparation such as jam and jelly. Ann. Bangladesh Agric. 28(1): 17-30